Comparing the Clinical Effectiveness of High-Dose and Low-Dose Statin Therapy in Patients with Atherosclerotic Coronary Artery Disease (CAD): Clinical Effectiveness of High-Dose and Low-Dose Statin Therapy in Atherosclerotic Disease - Ghafoor, Adnan; Rehman, Tanzil Ur; Sarfaraz, Maria; Rind, Aslam; Nasir, Ali; Khan, Jahanzeb Kamal; Shahzad, Shafqat (Pakistan Journal of Health Sciences, 2024)
Coronary artery disease is associated with the circulatory system and leading cause of death around the globe, Objective: To compare the mean changes in low-density lipoprotein cholesterol with high and low doses of statin therapy. Methods: A non-randomized controlled trial at the Department of Cardiology, Fauji Foundation Hospital Rawalpindi was conducted from January 26-2023 to July 25-2023, among patients aged 45-75 years of both genders with ST-elevation myocardial infarction or non-ST-elevation myocardial infarction. Patients were divided into groups using a convenience sampling technique. Patients in Group A were given high-dose statin therapy atorvastatin 40mg orally daily. While Group B received low-dose statin therapy atorvastatin 20mg orally daily. The low-density lipoprotein cholesterol level was repeated after 3 months. Data were entered and analyzed using SPSS version 23. Results: The mean age of Group A was 56.14 ± 8.9 years and Group B was 57.5 ± 9.7 years, as per gender distribution group A showed 57.1% and Group B 68.6%, whereas, the females in Group A, were calculated as 42.9% and in Group B 31.4%. The mean changes observed in low-density lipoprotein cholesterol were significantly higher in groups in comparison to the group with low-dose statin therapy. The changes observed were significant at 35 ± 27.8mg/dl in higher statin therapy versus 21.4 ± 20 mg/dl with a p-value of 0.024. Conclusions: It was concluded that high-dose statin causes a greater reduction in low-density lipoprotein cholesterol levels. The high-dose therapy could be a great option in treating the low-density lipoprotein in initial management.